Application of the water table fluctuation method to characterize groundwater recharge in the Pampa plain, Argentina - Varni, Marcelo (2013)
The water table fluctuation (WTF) method is based on accepting that rises of a water table are due to recharge water reaching the groundwater. To apply the method, an estimate of the specific yield of the zone of fluctuation of the groundwater level is required. In this paper, a method for estimation of the specific yield (S y ) is proposed; it consists of a graphical procedure which relates rises in groundwater level to the  precipitation from which they originated. The method presents more reliable S y values as the number of events measured increases. Eighteen years of daily measurements were analysed to obtain a S y value of 0.09, which was used to apply the WTF method. The obtained recharge values show consistency with values calculated by other authors for the same region.